Big wonderful thing : a history of Texas - Harrigan, Stephen, 1948- (Harrigan, Stephen, 1948- Texas bookshelf., 2019)
A tour de force by a New York Times best-selling author and master storyteller who captures the rich history of a state that sits at the center of the nation, yet defiantly stands apart.